M-Mode Ultrasound as a Portable Alternative to Fluoroscopy in Evaluation of Diaphragmatic Motion: Technical Note - Chandola, Stuti; Jana, Manisha; Naranje, Priyanka; Bhalla, Ashu Seith (Indian Journal of Radiology and Imaging, 2022)
Diaphragmatic structure and function assessment can be performed using grayscale as well as M-mode ultrasound. This article discusses the application of M-mode ultrasound in the assessment of diaphragmatic dysfunction.
Keywords: diaphragm; M mode; ultrasound